Past dominations, current informal institutions and the Italian regional economic performance - Adriana Di Liberto; Marco Sideri (European Regional Science Association (ERSA), 2013)
We study the connection between economic performance and the quality of government institutions for the sample of 103 Italian NUTS3 regions, including new measures of institutional quality calculated using data on the provision of four areas of public service: health, educational infrastructures, environment and energy. In order to address likely endogeneity problems, we use the histories of the different foreign dominations and their bureaucracies that ruled Italian regions between the 16th and 17th century and over seven hundred years before the creation of the unified Italian State. Our results suggest a significant role of past historical institutions on the current public administration quality and show that the latter makes a difference to the economic performance of regions. Overall, our analysis confirms that informal institutions matter for development, and that history can be used to find suitable instruments.
Keywords: O43; C26; 330; economic development; quality of government; informal institutions; history; weak instruments